Integrated membraneâelectrocoagulation system for removal of celestine blue dyes in wastewater - Saad, M.S. (MDPI AG, 2020)
The textile industry provides for the needs of people especially in apparel and household items. The industry also discharges dye-containing wastewater that is typically challenging to treat. Despite the application of the biological and chemical treatments for the treatment of textile wastewater, these methods have their own drawbacks such as non-environment friendly, high cost and energy intensive. This research investigates the efficiency of the celestine blue dye removal from simulated textile wastewater by electrocoagulation (EC) method using iron (Fe) electrodes through an electrolytic cell, integrated with nylon 6,6 nanofiber (NF) membrane filtration for the separation of the flocculants from aqueous water. Based on the results, the integrated system achieves a high dye removal efficiency of 79.4, by using 1000 ppm of sodium chloride as the electrolyte and 2 V of voltage at a constant pH of 7 and 10 ppm celestine blue dye solution, compared to the standalone EC method in which only 43.2 removal was achieved. Atomic absorption spectroscopy analysis was used to identify the traces of iron in the residual EC solution confirming the absence of iron. The EC-integrated membrane system thus shows superior performance compared to the conventional method whereby an additional 10â30 of dye was removed at 1 V and 2 V using similar energy consumptions. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.